The history augmented Solow model - Carl-Johan Dalgaard; Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
Unified growth theory predicts that the timing of the fertility transition is a key determinant of contemporary comparative development, as it marks the onset of the take-off to sustained growth. Neoclassical growth theory presupposes a take-off, and explains comparative development by variations in (subsequent) investment rates. The present analysis integrates these two perspectives empirically, and shows that they together constitute a powerful predictive tool vis-a-vis contemporary income differences.
Keywords: O11; O57; 330; comparative development; unified growth theory; neoclassical growth theory